Effect of Botulinum Toxins Injection on Liver Enzyme and Histochange of Liver and Kidney of Female Rats - Rana Talib Al-Muswie (Journal of Global Pharma Technology, 2016)
The present work aimed to study the effect of Botulinum toxins on liver enzyme ,Urea ,Creatinine and histological change of liver and kidney .Two doses 0.1 and 0.2 ml of Botulinum toxins were used and the animals were injected Intramuscular administration of botulinum toxin for 1 day as two dose only. The alanine aminotransferase (ALT) level in the rats of the control group (A) is significantly lower (P<0.05) than both the rats group (B) treated with Botulinum toxins and group(C). The aspartate aminotransaminase (AST) level in the rats of the control group is significantly lower (P<0.05) than both the rats treated with Botulinum toxins. Also, The results showed a significant increase in the level of urea and Creatinine of the female rats treated with Botulinum toxins compared with control group, In the histologicaly, the results showed vaculation in hepatocytes, and infiltration of inﬂammatory cells in liver of group (B), while in group (C), there was inﬂammatory cells, detachment of some hepatocytes, and congestion in area of Portia,. Kidney of group B showed congestion of blood cells and increase number of nuclei. In kidney of group C there was an increase in the number of nuclei, edematous glomerulus, and glomerular lobulation.Keywords: Botulinum toxins; Liver Enzyme, Urea, Creatinine, Liver, Kidney.